A carbon nanotube-based textile pressure sensor with high-temperature resistance. Issue 36 (16th August 2022) - Chen, Yankun; Yan, Xue; Zhu, Yanlong; Cui, Meng; Kong, Lei; Kuang, Minxuan; Zhang, Xiuqin; Wang, Rui
Abstract : A textile pressure sensor with high-temperature resistance, which can work at temperatures up to 300 °C and withstand a high temperature of 900 °C in N2, was fabricated by printing multi-wall carbon nanotubes (MWCNTs) electrodes on quartz fabrics. Abstract : Textile pressure sensors capable of withstanding high temperatures have attracted increasing interest due to their potential applications in harsh conditions. In this work, a textile pressure sensor with high-temperature resistance was realized based on multi-wall carbon nanotubes (MWCNTs) and quartz fabrics. The textile pressure sensors exhibited low fatigue over 20 000 cyclic loadings. Owing to the high-temperature resistance of MWCNTs and quartz fabrics, the textile sensor can work at temperatures up to 300 °C and can maintain good sensitivity after calcination at 900 °C in N2 for 30 min. This work provides a simple, facile, and inexpensive method for fabricating textile pressure sensors with high-temperature resistance.